Analysing deltamethrin susceptibility and pyrethroid esterase activity variations in sylvatic and domestic Triatoma infestans at the embryonic stage - Santo Orihuela, Pablo Luis (2013)
The aim of the present work was to study the deltamethrin susceptibility of eggs from populations of Triatoma infestans and contribution of pyrethroid esterases to its degradation. Insects were from sylvatic areas Veinte de Octubre and Kirus-Mayu (Bolivia) and from domiciliary areas El Palmar (Bolivia) and La Pista (Argentina). Susceptibility was determined by dose-response bioassays. Serial dilutions of deltamethrin (0.0005 to 1 mg/ml) were topically applied on 12 days old eggs. El Palmar showed the highest Lethal Doses Ratio (LDR) value (44.90) compared with NFS reference strain whereas Veinte de Octubre showed the lowest value (0.50). Pyrethroid esterases were evaluated using 7-coumaryl permethrate (7-CP) on individually homogenized eggs of each population and NFS. El Palmar and La Pista showed values of 40.11 and 36.64 pmol/min/mg protein, statistically similar to NFS (34.92 pmol/min/mg protein) and different from Kirus-Mayu and Veinte de Octubre (27.49 and 22.69 pmol/min/mg protein). The toxicological data indicate that the domestic populations are resistant to deltamethrin but no statistical contribution of 7-CP esterases was observed. Sylvatic populations showed values of LDR similar to NFS but lower activities of 7-CP esterases. This is the first study of pyrethroid esterases on eggs of Triatoma infestans using a specific substrate (7-CP).